Free Radical Scavenging, Anti-Infectious, and Toxicity Activities from Stenochlaena palustris (Burm.f.) Bedd. Extracts - Rudi Hendra; Rohimatul Khodijah; Muhammad Almurdani; Yuli Haryani; Ari Satia Nugraha; Neni Frimayanti; Hilwan Yuda Teruna; Rizky Abdulah (Advances in Pharmacological and Pharmaceutical Sciences, 2022)
Stenochlaena palustris (Burm.f.) Bedd. (Blechnaceae) or Kelakai is a traditional medicinal plant found in the Indonesian islands of Borneo and Sumatra. It has been used to treat wound healing, infection, and diabetes. This study looked into the free radical scavenging activity, antiplasmodial activity, toxicity, and antibacterial activity against pathogenic bacteria. The species’ aerial part was extracted with methanol, followed by a liquid-liquid extraction against (n-hexane, dichloromethane, and ethyl acetate). The extracts’ free radical scavenging activities were determined using DPPH and NO radicals. The antiplasmodial and toxicity assays were conducted using two Plasmodium falciparum strains (3D7 and W2) and the brine shrimp lethality test. In addition, antibacterial activity was determined using the well diffusion method. The results revealed that ethyl acetate depicted potential activities toward the assay. The ethyl acetate showed potential free radical scavenging activities with an IC50 value of 51.63 ± 0.46 μg/mL (DPPH) and 60.03 ± 0.65 μg/mL (NO). The antiplasmodial activities showed that the ethyl acetate had potential activities among the extracts with an IC50 value of 11.06 ± 0.45 μg/mL. However, all the extracts demonstrated nontoxic toward Artemia salina with LC50 > 1000 μg/mL. Furthermore, the ethyl acetate demonstrated intermediate susceptibility against B. cereus ATCC 10876, V. parahaemolyticus ATCC 17802, L. monocytogenes ATCC 7644, and S. Typhimurium ATCC 14028 at a concentration of 500 μg/disc. According to these findings, the ethyl acetate extract of S. palustris (Burm.f.) Bedd is a promising source of natural antioxidants and antiplasmodial agents.